1995
DOI: 10.1007/bf03172919
|View full text |Cite
|
Sign up to set email alerts
|

How to use preconceptions? The contact strategy dismantled

Abstract: The effects of the contact strategy (a computer-assisted instructional strategy aimed at conceptual change in text processing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…Inspired by these theories Ali (1990) and Biemans (Biemans & Simons, 1995,1996 created an instructional strategy (the CONTACT strategy) consisting of "ve steps. Students should be (1) helped in searching their own relevant pre-conceptions (through an exposing event); (2) stimulated to compare their pre-conceptions with the new information; (3) asked to formulate the new idea; (4) asked to apply the new conception in a concrete problem and (5) asked to evaluate the adequacy of the new conception in relation to step 4.…”
Section: Dealing With Prior Knowledge Of Learnersmentioning
confidence: 99%
“…Inspired by these theories Ali (1990) and Biemans (Biemans & Simons, 1995,1996 created an instructional strategy (the CONTACT strategy) consisting of "ve steps. Students should be (1) helped in searching their own relevant pre-conceptions (through an exposing event); (2) stimulated to compare their pre-conceptions with the new information; (3) asked to formulate the new idea; (4) asked to apply the new conception in a concrete problem and (5) asked to evaluate the adequacy of the new conception in relation to step 4.…”
Section: Dealing With Prior Knowledge Of Learnersmentioning
confidence: 99%
“…The CONTACT strategy is based on an instructional model consisting of five steps (see for more details Ali, 1990;Biemans, 1994;Biemans and Simons, 1995): 1) searching for own preconceptions; 2) comparing and contrasting these preconceptions with the new information; 3) formulating new conceptions, based on the previous step; 4) applying the new conceptions; 5) evaluating the new conceptions, based on the previous step. This sequence of instructional steps is always performed twice.…”
Section: Introductionmentioning
confidence: 99%
“…In our first study, the effects of the various CONTACT steps were examined by dismantling the strategy (see for more details Biemans, 1994;Biemans and Simons, 1993;1995). Results indicated that the complete CONTACT strategy was more effective in promoting conceptual change than the three dismantled versions (especially for "highly familiar" fifth-and sixth-graders): students who had been assigned to the complete CONTACT condition constructed conceptions that represented the relations between the central physical geography concepts from the texts more accurately.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HEWSON und HEWSON (1984) empfahlen, die Lernenden dazu zu bewegen, altes und neues Wissen zu vergleichen und zu kontrastieren. ALI (1990) und BIEMANS (1997BIEMANS & SIMONS, 1995, 1996 Menschen setzen bei der Arbeit nicht alle ihre Kompetenzen ein. Organisationen neigen dazu, die Kompetenzen ihrer Beschäftigten zu unterschätzen (SENGE, 1991).…”
unclassified